Islamic Human Resource Management: Thematic Map and Research Cluster - Maulida, Syahdatul; Rusydiana, Aam Slamet (Management and Sustainability, 2023)
This study aims to examine the development of Islamic human resource management by analyzing scholarly literature indexed in the Scopus database published from 1997 to 2023. The research methodology utilized biblioshiny-R. The findings reveal a significant increase in the number of scholarly publications in 2017, reaching a total of 17 publications. In terms of geographical distribution, Indonesia stands out as a leader with 84 documents of scholarly publications. The peak of the annual average citations occurred in 2007, with approximately 6.2 citations per year. The "Journal of Management Development" recorded the highest number of publications. The main thematic areas in scholarly publications on Islamic resource management include aspects of "Islam," "competency," and "human resource management." Additionally, the research identifies research topics based on their density and centrality, and analyzes research clusters connected through co-occurrence network analysis. It is expected that the results of this research will make a significant contribution to the understanding of the development of Islamic human resource management literature.